Strategi guru dalam membentuk karakter peserta didik melalui kegiatan ekstrakurikuler pramuka - Ammar Rafi Anshori; Sri Marmoah; Suharno, Suharno (Didaktika Dwija Indria, 2022)
Abstract. The Purpose of this research are to know (1) The Strategic used by teacher to bulid character of students through scout extracurricular activities at SDN 04 Manisrejo, Madiun City (2) the obstacles in build character of students through scout extracurricular activities at SDN 04 Manisrejo, Madiun City (3) Efforts and Solutions to bulid character of students through scout extracurricular activities at SDN 04 Manisrejo, Madiun City. The Subjects were 37 students taken from grade 4 in SDN 04 Manisrejo, Madiun City. The methods used qualitative research. Data collected by interview, observation and triangulation. Analysis data technique used component analysis. The Results of this research are most of the students like scout extracurricular. Commonly when the students bored with the activities, more like running around and bothering friends but the teachers had methods to handle the situations that is among system. Among system poisoned of “Ing Ngarso Sing Tuladha”, “Ing Madya Mangun Karsa”, “Tut Wuri Handayani”.the students showed character in second week because there are 7 students who have not shown good character, so this solutions is teachers applying methods during scout extracurricular because during the research, researches find different behavior are getting better. Keyword. Teachers strategic, character, scout extracurricular